A Critical Analysis of the New Mining Company Town Kalumbila, Zambia - Graber, Andrea Katja (2020)
Mining company towns are concrete sites where the spatial government of mining companies and its consequences can be studied. In this thesis I did a qualitative case study on the new mining company town Kalumbila based on three months of field work between June and September 2019. Kalumbila is being developed next to a copper mine owned by First Quantum Minerals Ltd. (FQM) in the Northwestern Province of Zambia. It is a particularly interesting case to study, as it is presented as a model town, open to non-miner residents and investors and designed to be sustainable and outlive the mine’s lifespan. I analysed how FQM governs space and people in Kalumbila by examining the planning goals for the town, the access regime to town infrastructure and services, as well as the narratives and practices of residents. The analysis shows that there is a strong overlap between the work and private life of people in Kalumbila. This has contributed to a lack of privacy and trust among residents, which in turn has reduced their participation in the town community. Moreover, house sharing is a common practice in Kalumbila and has led to the fact that many residents see the town as a place of accommodation during work, rather than a new home. The research further demonstrates that hierarchies in the mining company are strongly influencing the social structures in Kalumbila, having resulted in the creation of spatially segregated and socially distinct groups. To which group a person belongs, determines his or her possibilities of accessing town infrastructure and services. Kalumbila presents thus a spatial imprint of the mining company hierarchies. By providing insight into the functioning of a new mining company town, this thesis contributes to an understanding of the socio-spatial transformations induced by large-scale mining operations in the Global South.